Application of different strategies to improve aerobic granular sludge process performance for treatment of municipal wastewater - Koşar, Şadiye (Graduate School, 2022)
Aerobic granular sludge (AGS) process is an energy-efficient alternative biological wastewater treatment process to the conventional activated sludge (CAS) process which requires high energy and big space. In CAS systems, flocs sized above 0.2 mm are referred as granule. So far flocs and granules could be easily differentiated by size clustering as well as their capabilities of removal for organic matter and nutrients. Surface of the granule has porous morphology, and this allows the substrate penetration and as well as oxygen diffusion into the inner layers of the granule. The diffusion of oxygen is somehow can be a limiting factor for the simultaneous carbon and nutrient removal due to structure of the granule. In many cases, granule has a compact and dense structure that limits the oxygen transfer to the inner core layers of the granule which improves the denitrification and allows better phosphorus (P) removal within the granule. Whereas in some situations, granules have amorphous structure which do not improve any core inside the granule so affects the removal of substrate. Aerobic granules are heavier than flocs formed in waste sludge, so they settle faster, and this improves the settleability of the sludge which further allows to operate in one reactor. For this reason, large sedimentation tanks are not required in AGS systems. Since aerobic, anoxic and anaerobic biological activities take place inside the granule, AGS process offers 25-75% less space and consumes 20-50% less energy compared to conventional activated sludge plants. Nitrification takes place on the surface of the granule during aeration phase and denitrification occurs in the inner layers of the granule under anoxic conditions. P removal is maintained by polyphosphate accumulating organisms (PAOs) that are located in the core part of the granule. PAOs and denitrifiers which are responsible for the denitrification are both heterotrophic organisms and compete for the carbon sources as substrate. For this reason, it is important to have sufficient amount of organic matter for nitrogen (N) and P removal. Since PAOs are located in the inner layer of the granule they are only capable of using organic that are in dissolved form. In municipal wastewater, organic matter is particulate and dissolved forms. Particulate matter reduces N and P removal up to 40% and 46% respectively. Particulate organic matter is turned into dissolved form in the presence of extracellular polymeric substances (EPS) which are hydrolyzing them further. Hydrolysis ends up in anaerobic phase when the attached particulate matter on the surface of the granules hydrolyzed and it is uptaken by PAOs and denitrifiers. If dissolved organic matter cannot be consumed by these species, then it would be consumed by the aerobic heterotrophic bacteria on the surface of the granule which further causes filamentous microorganisms' overgrowth. This leads to amorphous structure and disintegration of the granule. In this thesis, the treatability municipal wastewater by AGS process was investigated under different circumstances. Four separate studies were conducted within the scope of this study. In the first study, two different sludge were comparatively investigated as inoculum: (a) waste activated sludge (WAS) taken from the return activated sludge line of an advanced biological wastewater treatment plant (WWTP), (b) WAS taken from the return activated sludge line of a pilot scale high-rate activated sludge (HRAS) system. This study was conducted in two stages: AGS system was seeded with the WAS taken from the return activated sludge line of an advanced biological wastewater treatment plant in the first stage; in the second stage, AGS system was seeded with the mixture of WAS taken from the return activated sludge line of an advanced biological WWTP and WAS of pilot scale HRAS process as volume in proportion of 1:1. This study was performed to reveal the contribution of microorganisms found in the flocculent sludge to the granulation process. Since HRAS process sludge has high settleability and the mixture of WAS with HRAS process as inoculum was expected to enhance the settling properties of granular sludge as well as achieving good treatment performance. Although at the start-up period sludge wash-out occurred and mainly fluffy waste sludge wasted, HRAS process sludge settles faster, and it remained in the reactor. So, in this case especially denitrifiers were mostly washed out of the system which deteriorated system performance compared to the AGS system operated solely with WAS. At the end of this study, WAS waste sludge was chosen as seed sludge for the further studies to obtain aerobic granulation based upon AGS system treatment performance. In the second study, WAS taken from the return activated sludge line of an advanced biological WWTP was used as seed sludge. Study was conducted in two stages: (a) AGS system was fed directly with the synthetic municipal wastewater, (b) AGS system was fed with the pre-settled synthetic municipal wastewater (30 min of settling) to simulate pre-sedimentation tanks in the full-scale wastewater treatment plants (WWTPs). With pre-settling application, it was proposed that particulate matter would settle so mainly dissolved organic matter could be introduced to the AGS system. Since AGS system is anaerobically fed, this would improve the nutrient removal by allowing the uptake of organic matter easily by PAOs and denitrifiers. It was shown that up to 60% of particulate matter was removed by settling and as a result carbon/nitrogen (C/N) ratio decreased 20% lead deterioration of the AGS system treatment performance. It was apparent that a combination of pre-sedimentation in AGS process didn't improve the system. In the third study, AGS system was operated in three different stages continuously following each other without having different start-up periods: (a) AGS system was fed directly with raw municipal wastewater, (b) AGS system was fed with the pilot scale HRAS system's effluent (treated wastewater), (c) AGS system was fed with the mixture these two flows: raw municipal wastewater (20%) and HRAS process effluent (80%). Waste sludge taken from the return activated sludge line of an advanced biological wastewater treatment plant was used as inoculum. Firstly, aerobic granulation was maintained by introducing municipal wastewater than HRAS process effluent fed to the system and AGS system performance was followed thoroughly. It was shown that the granule stability remained somehow same, but AGS system performance was affected by decreased C/N ratio. AGS system was fed with the mixture the raw municipal wastewater and HRAS process effluent to improve the system performance. As a result, AGS system performance was improved with the increase in C/N ratio (20% increase compared to feeding with only HRAS process effluent). Thus, HRAS process integration with AGS process was found to be energy efficient configuration. Both systems comparably occupy less space than conventional treatment systems and their integration will definitely improve the effluent quality. In the fourth study, digestibility of AGS which was obtained from the third study was compared to the WAS taken from the return activated sludge line of an advanced biological wastewater treatment plant. It is known that AGS process sludge has low digestibility than WAS. Thus, ultrasonication was applied to improve the solubilization of organic matter for increasing sludge digestibility. Since aerobic granules are clusters of microorganisms that are attached together, they are bigger in size and more compact than WAS flocs. Therefore, relying on their physical differences, it was assumed that ultrasonication would enhance digestibility of the AGS. It was shown that ultrasonication as pre-treatment method led to solubilization for both sludge sources in terms of volatile fatty acids (VFAs), protein and carbohydrates besides causing decrease in particle size. A direct relation found between the release of organic compounds, ammonium, phosphorus and heavy metals with the increase in ultrasonication intensity. Overall results obtained from this thesis showed a comprehensive approach to treat municipal wastewater by AGS process while improving the treatment performance by focusing on inoculum source as well as feeding strategy. Besides, sludge from AGS process was evaluated in terms of soluble products release by applying ultrasonication process compared to the WAS. This thesis would enhance the knowledge on AGS technology in terms of seeding and feeding regimes beneath giving clues for full-scale AGS process applications.
Kentsel atıksu arıtımında aerobik granüler çamur prosesinin arıtma performansını iyileştirmek için farklı stratejilerin uygulanması
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: aerobic granular sludge; aerobik granüler çamur; wastewater; atıksu